Endoscopic Surgery under Fluoroscopic Guidance Is Useful for Diagnosing and Treating Epiphyseal Osteomyelitis Caused by Mycobacterium Species. (13th June 2018) - Ochi, Hironori; Taira, Katsuaki; Nemoto, Naho; Oikawa, Noboru; Nagao, Soya; Takano, Tadamasa; Kaneko, Kazuo
Abstract : Osteomyelitis caused by Mycobacterium species may be difficult to diagnose and treat. We report a case of treatment for osteomyelitis caused by Mycobacterium species in the epiphysis of the right proximal tibia. A 28-month-old boy presented to a hospital with symptoms of fever and right knee pain. He had been vaccinated with Mycobacterium bovis Bacille Calmette-Guérin (BCG) at five months of age. The epiphyseal radiolucent lesion had increased in size and extended to the metaphysis through the physis on a plain radiograph of the right proximal tibia. Surgical drainage and curettage of the lesion were performed with an endoscope under C-arm fluoroscopy. The intraoperative histopathological examination revealed granulation tissue composed of caseous necrosis and Langerhans giant cells, revealing Mycobacterium species to be the causative pathogen. Because of suspected osteomyelitis caused by BCG, the antituberculosis drugs were administered orally from an early postoperative stage. A plain radiograph taken eight months postoperatively showed bone regeneration in the area of curettage and a slight physeal bridge, in addition to normalization of the inflammatory response on blood sampling. It was possible to perform accurate diagnosis and rapid treatment for epiphyseal osteomyelitis caused by Mycobacterium species using endoscopic surgery under fluoroscopic guidance.